Peningkatan Pengetahuan tentang Periksa Payudara Sendiri (SADARI) sebagai Upaya Deteksi Dini Kanker Payudara di SMA Setia Dharma Palembang - Devina Anggrainy Dencik (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The World Health Organization (WHO) states that cancer is the biggest cause of death in the world. The highest incidence of cancer and the most common cause of death is breast cancer. In 2020, global data shows that 2.3 million women were diagnosed with breast cancer, with 685,000 deaths. One of the causes of breast cancer is delay in early detection. The aim of this community service activity is to increase the knowledge and skills of Setia Dharma Palembang High School female students in carrying out BSE as an effort to detect breast cancer early. The methods used are lectures, demonstrations and simulations as well as educational videos. The results of the activity showed an average pretest score of 52.3 and an average posttest score of 76.4. These results indicate an increase in the knowledge of counseling participants after being given education about BSE. For the results of the female students' ability to do BSE based on the observation sheet, the results obtained were that of the 53 female students, 71.7% were able to do BSE correctly and 28.3% were unable to do BSE correctly. It is hoped that all related parties will work together well in efforts to reduce the incidence of breast cancer.